Prospects and challenges for incorporating trees into urban infrastructural developments in Nigeria (2008)
Nigeria’s major cities are characterised by huge and growing social and environmental problems,such as air, land and noise pollution; non-conducive local micro climatic conditions; and stressful social and psychological living environments. These result from in- adequate, dilapidated and overstretched infrastructure, degraded urban physiognomy, increasing levels of unemployment, crime, insecurity and other social vices. These, in addition to inherent technical and economic constraints, make the in corporation of trees into the social and physical fabric of overall planning of towns and cities in Nigeria imperative. This is a natural and cost-effective means of alleviating environmental, social and economic problems in many of the Nigerian major cities. Successful integration of trees/ forests into overall urban planning will require the development of appropriate information, policy, administrative and legal frameworks, enlistment of social and political support, as well as appraisal of technical feasibility and environmental suitability of incorporation into the urban landscape. More importantly, sustainable urban forestry development in Nigeria will of necessity require the availability and readiness of NGOs to spearhead an urban forestry movement in the country.